The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.2139/ssrn.1547823
|View full text |Cite
|
Sign up to set email alerts
|

Do Wage Cuts Damage Work Morale? Evidence from a Natural Field Experiment

Abstract: Employment contracts are often incomplete, leaving many responsibilities subject to workers' discretion. High work morale is therefore essential for sustaining voluntary cooperation and high productivity in firms. We conducted a field experiment to test whether workers reciprocate wage cuts and raises with low or high work productivity. Wage cuts had a detrimental and persistent impact on productivity, reducing average output by more than 20 percent. An equivalent wage increase, however, did not result in any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
157
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(176 citation statements)
references
References 41 publications
16
157
1
2
Order By: Relevance
“…The specifics of our design are more in line with Maximiano et al (2007) though. Like in that paper we let subjects play the gift-exchange game only once, rather than repeatedly in a row.…”
Section: Experimental Designmentioning
confidence: 87%
See 2 more Smart Citations
“…The specifics of our design are more in line with Maximiano et al (2007) though. Like in that paper we let subjects play the gift-exchange game only once, rather than repeatedly in a row.…”
Section: Experimental Designmentioning
confidence: 87%
“…Compared to Fehr et al (1998) and Maximiano et al (2007) the payoff functions that we use here differ in two notable ways. First, the marginal returns to effort are four times higher, i.e.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field, psychologists found that a waitress with a broad smile receives greater tips (Tidd & Lockard, 1978), while economists have found that kind acts are rewarded in the context of charitable donations (Falk, 2007). Both economists and psychologists have also found negative reciprocity, for example, in the context of wage cuts (Greenberg, 1990;Kube, Marechal & Puppe, 2010). Several theoretical models complement these investigations (e.g., Cox et al, 2007;Dufwenberg & Kirchsteiger, 2004;Falk & Fischbacher, 2006).…”
Section: Introductionmentioning
confidence: 91%
“…Recent studies …nd mostly moderate support for positive reciprocity. See for instance Gneezy and List (2006), Cohn et al (2009), Kube et al (2010), Bellemare and Shearer (2009) and Hennig-Schmidt et al (2010). 4 See for instance "Performance Reviews: Many Need Improvement" in the New York Times (September 10, 2006).…”
Section: Introductionmentioning
confidence: 99%